Narcissism and the experience of pain. (1st February 2021) - Brunell, Amy B.; Buelow, Melissa T.; Trost, Zina
Abstract: In the present set of studies, narcissism and painful experiences were examined. In Study 1, kinesiophobia and pain catastrophizing were assessed. In Study 2, participants experienced a socially painful experience via the game of Cyberball and were given a set of cognitive tasks to complete. In Study 3, participants' reactions to experiencing a physically painful experience (a cold pressor task) were examined. Results indicated that vulnerable narcissists were more concerned about having physically painful experiences, but did not report greater pain when having an actual physically painful experience. Vulnerable narcissists also reported negative affect following negative experiences of physical and social pain (in addition to more need threat). Grandiose narcissists appeared to be less concerned about having physically painful experiences. Although grandiose narcissism was not associated with experiencing physical pain, it was associated with worse mood from experiencing pain. When experiencing a socially painful experience, they reported being relatively unaffected and were not overly distracted from cognitive tasks. The facets of narcissism such as psychological entitlement, interpersonal exploitativeness, and grandiosity were also explored.